Chapter EIGHT Writing Revelation The Book of Margery Kempe - Saunders, Corinne (Boydell & Brewer, 2019)
This essay addresses intersections of gender and genre by exploring the complex ways in which the Book of Margery Kempe draws on other devotional texts, particularly those of Hilton and Rolle, on the lives of holy women, and on Kempe's own social and cultural contexts, in order to shape a unique type of life-writing. Attention is paid to the multi-modal sensory quality of Kempe's visionary experience, and to the privileging of voice across the book. Topics addressed include the ways in which affective and cognitive combine in Kempe's experience, the difficulty of placing inner experience, the paradoxes inherent in attempting to express the ineffable, and the radical quality of her attempt to write an inner life.